Haw, haw de karabaw
Living a simple lifestyle in the Barrio of Maisan farming a small-sized field. Sebyo has no other inspiration aside from Coring (Dang Cecilio). Her homecoming to serve as their new Municipal Health Officer ( as a full-pledge doctor) started the thrill, excitement and slight complication to Sebyo's life not to mention the hidden treasure said to be buried at the backyard of Coring and Tiya Belen's (Dely Atay-Atayan) house.